2011
DOI: 10.1002/jcb.23320
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic protection afforded by cardioplegic celsior and histidine buffer solutions to hearts subjected to ischemia and ischemia/reperfusion

Abstract: Cardiomyocytes undergo apoptosis in response to ischemia and ischemia/reperfusion (I/R). During heart preservation, inhibition of apoptosis is critical to avoid organ failure. We aimed to compare the protection afforded by Celsior (Cs) and Histidine buffer solution (HBS) against apoptotic signaling in hearts subjected to moderate (4 h) versus severe (6 h) ischemia alone or followed by 30 min reperfusion. The impact of gender on cardioplegic protection was also explored. Hearts from male and female Wistar-Han r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Examples of such strategies are provided by demonstrations that pharmacological interventions which negatively regulate apoptosis -particularly through effect on mitochondrial function are cardioprotective following I/R injury (27,28). A very intriguing study of the phenomenon of cardiovascular "necropoptosis" in a guinea pig model demonstrated that simultaneous inhibition of necroptosis and apoptosis exhibited additiveand possibly synergistic resistance to I/R damage (29).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such strategies are provided by demonstrations that pharmacological interventions which negatively regulate apoptosis -particularly through effect on mitochondrial function are cardioprotective following I/R injury (27,28). A very intriguing study of the phenomenon of cardiovascular "necropoptosis" in a guinea pig model demonstrated that simultaneous inhibition of necroptosis and apoptosis exhibited additiveand possibly synergistic resistance to I/R damage (29).…”
Section: Discussionmentioning
confidence: 99%
“…Western Blot procedure was performed as previously described by Alves et al . (). The resulting membranes were incubated with rabbit anti‐GLUT1 (1 : 300, CBL242), rabbit anti‐GLUT3 (1 : 1000, ab41525), rabbit anti‐PFK1 (1 : 500, Sc67028), rabbit anti‐MCT4 (1 : 1000, Sc50329), rabbit anti‐LDH (1 : 10000, ab52488) and rabbit anti‐ALT (1 : 500, Sc99088).…”
Section: Methodsmentioning
confidence: 97%
“…The most significant pathways were p53 signaling pathway [26,27] (p = 4.72E-04) and complement and coagulation cascades [28] (p = 6.20E-04). Meanwhile, the DEGs enriched in these two pathways included CCNB1, CDC2, SERPINE1, A2M and FGG.…”
Section: Resultsmentioning
confidence: 99%